URDU-POVERTY ALLEVIATION AND ISLAMIC WELFARE STATE (An analytical study according to Islamic teachings) - Atiq ullah; Ruqia Bano (دی اسکالر)
Poverty is a dangerous social problem which puts man under trial dissuading him from his religion and compromising his dignity and character. It is a potential threat to the peace and stability of society. Islam has enjoined upon the state as well as community to share the responsibility of eliminating poverty from society. The Quran and the Sunnah identify the ways and means by which this responsibility should be carried out. The economic philosophy of Islamic aims, in the first place, to eliminate poverty by providing the basic human needs, narrowing the gap between the rich and the poor, and developing the resources of the earth for the welfare of human beings for whom every thing in heaven and earth is made subservient.within the boundaries of its economic philosophy. Islam has contrived many ways to care the problem of poverty. Some of these are responsibility of the Islamic welfare state, others are to be fulfilled by the society and some are shared obligation of both Islamic welfare state and society.